Bacterial cellulose - properties and its potential application - Betlej, Izabela; Sarani Zakaria,; Krajewski, Krzysztof J.; Boruszewski, Piotr (Penerbit Universiti Kebangsaan Malaysia, 2021)
This review paper is related to the utilization on bacterial cellulose in many applications. The polymer produced from bacterial cellulose possessed a very good physical and mechanical properties, such as high tensile strength, elasticity, absorbency. The polymer from bacterial cellulose has a significantly higher degree of polymerization and crystallinity compared to those derived from plant. The collection of selected literature review shown that bacterial cellulose produced are in the form pure cellulose and can be used in many of applications. These include application in various industries and sectors of the economy, from medicine to paper or electronic industry.